Dental Radiographic/Digital Radiography Technology along with Biological Agents in Human Identification. (18th January 2022) - Yazdanian, Mohsen; Karami, Shahryar; Tahmasebi, Elahe; Alam, Mostafa; Abbasi, Kamyar; Rahbar, Mahdi; Tebyaniyan, Hamid; Ranjbar, Reza; Seifalian, Alexander; Yazdanian, Alireza
Abstract : The heavy casualties associated with mass disasters necessitate substantial resources to be managed. The unexpectedly violent nature of such occurrences usually remains a problematic amount of victims that urgently require to be identified by a reliable and economical method. Conventional identification methods are inefficient in many cases such as plane crashes and fire accidents that have damaged the macrobiometric features such as fingerprints or faces. An appropriate recognition method for such cases should use features more resistant to destruction. Forensic dentistry provides the most appropriate available method for the successful identification of victims using careful techniques and precise data interpretation. Since bones and teeth are the most persistent parts of the demolished bodies in sudden mass disasters, scanning and radiographs are unrepeatable parts of forensic dentistry. Forensic dentistry as a scientific method of human remain identification has been considerably referred to be efficient in disasters. Forensic dentistry can be used for either "sex and age estimation, " "Medical biotechnology techniques, " or "identification with dental records, " etc. The present review is aimed at discussing the development and implementation of forensic dentistry methods for human identification. For this object, the literature from the last decade has been searched for the innovations in forensic dentistry for human identification based on the PubMed database.